Examining the impact of sex-biased information on health behaviors: a study of HPV vaccination among male college students based on the extended theory of planned behavior - Wang, Tong-Chen Lucas; Zhang, Mei-Juan; Zhang, Hualin (Frontiers in Public Health, 2025)
IntroductionHuman papillomavirus (HPV) is an exceptionally transmissible virus with a widespread presence that represents a considerable public health concern. Notably, the existing information landscape regarding HPV vaccination tends to favor female perspectives, which may inadvertently neglect the risks associated with HPV infection in men-particularly among male college students, who constitute a vulnerable demographic. To address this gap, effective health communication strategies are essential to encourage vaccination behaviors. This study seeks to extend the Theory of Planned Behavior (TPB) to investigate how sex-biased information influences the HPV vaccination intentions of male college students.MethodsA survey involving 240 participants was conducted to analyze the correlation between the HPV vaccine information environment and vaccination intentions. Utilizing Structural Equation Modeling (SEM), we assessed both direct and indirect effects that shape this relationship.ResultsFindings reveal that sex-biased HPV vaccination information can have both direct and indirect effects on the vaccination behaviors of male university students. Specifically, attitudes towards the vaccine positively influence the willingness to receive free vaccinations, while subjective norms and perceived behavioral control positively impact the intention to obtain both paid and free vaccinations.DiscussionThis study highlights that the female-oriented focus of HPV vaccination information, which underscores feminine norms, may limit the effectiveness of HPV health education for male college students. Additionally, price considerations have a limiting impact on the favorable attitudes of male university students towards vaccination. Conversely, male-targeted informational campaigns that heighten perceptions of HPV-related risks can diminish price sensitivity regarding vaccines, ultimately fostering increased willingness to vaccinate. The paper concludes by suggesting avenues for future research aimed at developing health communication strategies to enhance HPV vaccination rates among men. Implications and limitations are discussed.